Contemporizing Maqāṣid Sharīʿah: Reinterpreting Ḥifẓ al-Māl in Response to Personal Data Monetization - Amirudin Nur Wahid; Ahmad Nashrullah; Dedi Dores (Indonesian Journal of Law and Islamic Law (IJLIL), 2026)
Personal data is an interesting topic in today's digital era. Data is not only a pile of codes, numbers, or symbols, but can also be processed. Personal data processing is used by various sectors to maximize the potential and opportunities in developing existing businesses. The form of data use is often done through data monetization which is useful as a consideration for more accurate data-based decision making. However, there are many incidents of data theft or data misuse that are not in accordance with the principles of data protection. Therefore, it is necessary to contemporize maqāṣid syarīʿah in viewing personal data as property. The purpose of this study is to find the concept of monetization of personal data in accordance with the meaning of property in maqāṣid sharīʿah. This contemporization is useful in building legal insights based on the principles of maqāṣid sharīʿah. This research is a normative legal research (juridical normative) by collecting data through literature study related to data monetization. To answer these problems, this research uses a conceptual approach and a statutory approach. The data obtained were then analyzed qualitatively. Based on the results of this study, it can be found that data is recognized as property in maqāṣid syarīʿah. The reason personal data can be said to be a treasure in maqāṣid sharīʿah is because it has fulfilled the same characteristics as treasure. First, data has a beneficial value derived from data monetization. Second, data has economic value in its use. Third, data has legal legislation that protects it. The enactment of personal data in maqāṣid sharīʿah is a contemporization of Islamic law that is able to answer various problems of the times.